Multi‐organ dysfunction scoring in neonatal encephalopathy (MODE Score) and neurodevelopmental outcomes. (22nd September 2021) - Sweetman, Deirdre Una; Strickland, Tammy; Isweisi, Eman; Kelly, Lynne; Slevin, Marie Therese; Donoghue, Veronica; Meehan, Judith; Boylan, Geraldine; Murphy, John Finbar Anthony; El‐Khuffash, Afif; Molloy, Eleanor J.
Abstract: Aim: Neonatal encephalopathy (NE) is associated with an increased risk of multi‐organ injury. The lack of standardised definitions for multi‐organ dysfunction in NE hinders accurate quantification of these complications. Methods: A simple multi‐organ dysfunction in neonatal encephalopathy scoring (MODE) system was created to include the cardiovascular, respiratory, gastrointestinal, haematological and neurological systems with a maximum score of 15. The MODE score was then compared with the grade of NE, Bayley Scales of Infant Development (Bayley‐III) at 2 years of age and mortality. The Bayley score was used as it gave an objective score making it easier to compare the MODE score. Bayley score of <90 and/or abnormal MRI as an adverse outcome. Results: Infants with perinatal asphyxia (PA: n = 85) were prospectively enrolled (PA only n = 9; NE I = 23; NE II = 42; NE III = 11). Infants with higher MODE scores were significantly more likely to have moderate/severe NE (NE II/III: median scores (IQR) 7(5–10) versus mild NE 2 (1–3); p ‐value < 0.001) The MODE score was highly predictive of mortality (AUC 0.96, p ‐value = 0.002). Infants who had an abnormal neurological examination at discharge or abnormal Bayley‐III scores had significantly higher MODE scores ( p ‐value = 0.001). Conclusion: Quantifying multi‐organ injury is important to plan optimal early management and long‐term follow‐up. Additional use of clinical biomarkers may be useful as surrogate endpoints in future clinical trials and link to multi‐organ longer‐term developmental follow‐up.